A novel text steganography technique to Arabic language using reverse fatah - Shah, Asadullah; Memon, Mujtaba S (The Institute of Business Management, 2011)
This paper presents a new technique for information hiding in Arabic language. The technique uses text steganography to hi de the information. Considering the existence of Harakat(Fatha, Kasra and Damma) in the languages a new approach of reversing the Fatha has been developed for message hiding.The technique has been also evaluated to ensure its quality. This technique can be applied on other languages like Persian, Sindhi and other Regional languages